Teatro na terceira idade: costurando vidas em cena - FIGUEIREDO, Amanda Carneiro (2021)
Theater in the Elderly Age: Sewing Lives in Scene, records in five personal letters, each with a different recipient, the course of the student Amanda Carneiro Figueredo, while scholarship and trainee of the Extension Project Theater, Memory, Music and Poetry in the Best Age.Through a subjective perspective - interspersed with descriptions and reflections, memories and emotions, which seeks to approach various fields of knowledge, such as the artistic, empirical and scientific - this work presents considerations about the insertion of the elderly in the theatrical universe as protagonist of the scene and about dealing with the memory of old people through the theater; discusses the work of a theater teacher in gestation; about a theater workshop with seniors based on the games of Augusto Boal and about a theatrical production made from this workshop; about the relationship of the writer with her colleagues, her students, the context in which the project was developed and her intimate observations.With a free handwriting, a gazing now and then, this study brings together perspectives and create your own Knowledge Retouching Quilt.